2014
DOI: 10.3389/fgene.2014.00181
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of unique domains of Src family kinases

Abstract: Members of the Src family of kinases (SFKs) are non-receptor tyrosine kinases involved in numerous signal transduction pathways. The catalytic, SH3 and SH2 domains are attached to the membrane-anchoring SH4 domain through the intrinsically disordered “Unique” domains, which exhibit strong sequence divergence among SFK members. In the last decade, structural and biochemical studies have begun to uncover the crucial role of the Unique domain in the regulation of SFK activity. This mini-review discusses what is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 53 publications
1
80
0
2
Order By: Relevance
“…We also showed that EGF stimulated c-Src phosphorylation at Y418. Src plays diverse functions in cell signaling such as cell proliferation, differentiation, apoptosis, migration, and metabolism [54].…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that EGF stimulated c-Src phosphorylation at Y418. Src plays diverse functions in cell signaling such as cell proliferation, differentiation, apoptosis, migration, and metabolism [54].…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage is expected to generate two truncated fragments: (i) a truncated Src fragment (ΔNSrc) containing the SH2, SH3 and kinase domains and the C-terminal tail and (ii) a short N-terminal fragment consisting of the SH4 domain and a large portion of the Unique region, which were previously found to adopt highly disordered conformations ( Figure 6E) (Arbesu et al, 2017;Perez et al, 2009). Since the SH4 domain and Unique region are critical to anchoring of Src to plasma membrane and intracellular vesicular membrane (Amata et al, 2014;Arbesu et al, 2017), most ΔNSrc resides in the cytosol of neurons (Hossain et al, 2013).…”
Section: Most Proteolytically Processed Proteins In Excitotoxic Neuromentioning
confidence: 99%
“…Therefore, the results presented above preliminarily suggest that miR-3064-5p has antiangiogenic effects and could function as a novel and promising prognostic predictor for HCC. 18 Therefore, the expression and activity of Src is critical for cell growth, proliferation, etc. Multiple studies have demonstrated that FOXA1 plays an oncogenic role and is expressed highly in several tumors, such as esophageal and lung cancer, thyroid cancer, prostate cancer, breast cancer, osteosarcoma, HCC, etc.…”
Section: Variablesmentioning
confidence: 99%